2014
DOI: 10.1108/jsbed-06-2013-0086
|View full text |Cite
|
Sign up to set email alerts
|

Innovation culture in small Tunisian ICT firms

Abstract: Purpose – The research aims to ask whether, in the absence of overarching innovative conditions, a small firm can have an innovative culture and what its scale and scope is. Design/methodology/approach – The study employs four exploratory case studies. This methodological choice is justified in that a case study approach allows the use of the existing literature without inhibiting the detection of any unique characteristics in the Tunisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 85 publications
2
8
0
3
Order By: Relevance
“…In the same vein, Shanker, Bhanugopan, van der Heijden, & Farrell, (2017) added that organizational innovation culture set to become a vital aspect in framing innovation supporting a climate that promotes managerial innovation behavior. However, in line with previous studies that associated innovation culture with the different organizational outcomes like organizational performance (Padilha & Gomes, 2016),organizational innovativeness (Harbi et al, 2014), product development (Sattayaraksa & Boon-itt, 2016), resistance to change (Terziovski, 2010), we thus state the following hypothesis:…”
Section: Organizational Innovation Culture and Managerial Innovationsupporting
confidence: 69%
See 3 more Smart Citations
“…In the same vein, Shanker, Bhanugopan, van der Heijden, & Farrell, (2017) added that organizational innovation culture set to become a vital aspect in framing innovation supporting a climate that promotes managerial innovation behavior. However, in line with previous studies that associated innovation culture with the different organizational outcomes like organizational performance (Padilha & Gomes, 2016),organizational innovativeness (Harbi et al, 2014), product development (Sattayaraksa & Boon-itt, 2016), resistance to change (Terziovski, 2010), we thus state the following hypothesis:…”
Section: Organizational Innovation Culture and Managerial Innovationsupporting
confidence: 69%
“…However, this study sheds new light on how CEO TFL behavior stimulates managerial innovativeness within an organizational setting. Second, several studies associated innovation culture with different organizational positive outcomes, for instance, Dobni, (2008), linked innovation culture with performance outcomes, (Aksoy, 2017) found positive relationship between innovation culture and market performance, Harbi, Anderson, & Amamou, (2014) indicated that innovation culture enhance IT performance of SMEs. However, the relationship between organizational innovation culture and managerial innovation behavior is still missing in the literature.…”
Section: Page38mentioning
confidence: 99%
See 2 more Smart Citations
“…Eisenhardt (1989), por sua vez, ressalta que, quando se tem o propósito de construir teorias, os estudos de casos "combinam métodos de coleta de dados, tais como arquivos, entrevistas, questionários e observações" (p. 534), que podem se constituir em uma sugestão de estudos futuros sobre cultura de inovação. Entretanto pôde-se perceber, em três estudos mais recentes, que surgem pesquisas qualitativas com estudos de casos (Harbi, Anderson, & Amamou, 2014); grupos focais (Uzkurt, Kumar, & Ensari, 2013) e desenhos mais complexos de pesquisa, com estudos longitudinais como realizaram Wolf et al (2011) (1) .…”
Section: Considerações Finaisunclassified